2010
DOI: 10.1159/000323148
|View full text |Cite
|
Sign up to set email alerts
|

Nodular-Type Lichen Myxedematosus: A Case Report

Abstract: An 18-year-old Japanese woman noticed a progressive appearance of nodules on both forearms and on the left cubital fossa and left thigh one year before her initial consultation at our department. Physical examination showed elastic hard, slightly elevated, shiny and yellowish to skin-colored nodules of 6 to 10 mm in size on her extremities. From laboratory and histopathological findings, nodular-type lichen myxedematosus was diagnosed and nodules showed complete remission following local injection of triamcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 5 publications
(10 reference statements)
1
22
0
1
Order By: Relevance
“…There were no symptoms associated in four reported cases (Table 1). [33][34][35][36][37][38][39][40][41]…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…There were no symptoms associated in four reported cases (Table 1). [33][34][35][36][37][38][39][40][41]…”
Section: Figurementioning
confidence: 99%
“…Complete resolution of LM nodules has been reported with intralesional triamcinolone acetonide 0.02-0.05 mL (8mg/mL). 35 Destructive modalities including CO 2 laser, Erbium-YAG laser, cryotherapy, electrofulguration, and electrocoagulation are suitable for the localized forms for cosmetic reasons. 28 In HIV patients with associated DPLM, full resolution of papules and plaques has been reported after antiretroviral therapy.…”
Section: Treatmentmentioning
confidence: 99%
“…After 9 months of treatment with 0.03% tacrolimus ointment, the lesions did not show any improvement. No standard treatment for localized LM is available, although Azusa et al reported regression after triamcinolone acetonide injections. More case evaluations are needed for better management of nodular LM.…”
Section: Discussionmentioning
confidence: 99%
“…It is a rare disease, with only five cases reported in the literature. 1 Herein, we present a case related to ustekinumab.…”
Section: Introductionmentioning
confidence: 97%
“…Nodular lichen myxoedematosus is a localised form of lichen myxoedematosus. It is a rare disease, with only five cases reported in the literature 1 . Herein, we present a case related to ustekinumab.…”
Section: Introductionmentioning
confidence: 99%